2018
DOI: 10.1071/wf17147
|View full text |Cite
|
Sign up to set email alerts
|

Fuel and topographic influences on wildland firefighter burnover fatalities in Southern California

Abstract: Previous reviews of wildfires where a fatal firefighter burnover occurred have found that the incidents usually share similar characteristics in terms of the fire environment, such as steep slopes and complex topography (e.g. box canyons). Despite these similarities, systematic identification and communication of the locations where these conditions prevail are rare. In this study we used a presence-only machine-learning algorithm (Maximum Entropy, MaxEnt) coupled with spatial location information from past fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Research on firefighter safety has also been conducted following a number of incidents where firefighters perished during wildfire entrapment or burnovers (Cheney et al 2001;Page and Butler 2018;Viegas et al 2013;Xanthopoulos et al 2009). The aim was to investigate the factors that led to the incident and to develop improved protective measures and training for firefighters.…”
Section: Introductionmentioning
confidence: 99%
“…Research on firefighter safety has also been conducted following a number of incidents where firefighters perished during wildfire entrapment or burnovers (Cheney et al 2001;Page and Butler 2018;Viegas et al 2013;Xanthopoulos et al 2009). The aim was to investigate the factors that led to the incident and to develop improved protective measures and training for firefighters.…”
Section: Introductionmentioning
confidence: 99%
“…While it is at least theoretically possible to generate interpolated or meso-scale adjusted wind speed estimates using advanced models, topographic complexity-mountain ranges, elevation differences, wind-protected areas-pose challenges to accuracy. Page et al [48] tested the accuracy of the National Digital Forecast Database used by fire modelers with RAWS station measurements and found that the model tended to underestimate wind speeds when winds speed exceeded 4 ms −1 . More accurate downscaling might provide better weather inputs for future validation efforts.…”
Section: Assessment Of Representative Weather Inputs Vs Ffe's Defaultsmentioning
confidence: 99%
“…Although the times and locations where fires started within CONUS between 1992 and 2017 were seldom classified as having environmental conditions similar to those of HFD-SS entrapments, a high proportion of the area within large fire perimeters in the western GACCs, especially in southern California (South Ops), did have similar conditions. Southern California has an extensive history of firefighter entrapments [1,[62][63][64][65], with previous work showing a strong relationship between slope steepness and both the likelihood of an entrapment and subsequent fatalities [66,67].…”
Section: Common Environmental Conditionsmentioning
confidence: 99%